A Proteomic Approach Identifies Candidate Early Biomarkers to Predict Severe Dengue in Children. - Dang My Nhi; Nguyen Tien Huy; Kaname Ohyama; Daisuke Kimura; Nguyen Thi Phuong Lan; Leo Uchida; Nguyen Van Thuong; Cao Thi My Nhon; Le Hong Phuc; Nguyen Thi Mai; Shusaku Mizukami; Lam Quoc Bao; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Severe dengue with severe plasma leakage (SD-SPL) is the most frequent of dengue severe form. Plasma biomarkers for early predictive diagnosis of SD-SPL are required in the primary clinics for the prevention of dengue death. METHODOLOGY:Among 63 confirmed dengue pediatric patients recruited, hospital based longitudinal study detected six SD-SPL and ten dengue with warning sign (DWS). To identify the specific proteins increased or decreased in the SD-SPL plasma obtained 6-48 hours before the shock compared with the DWS, the isobaric tags for relative and absolute quantification (iTRAQ) technology was performed using four patients each group. Validation was undertaken in 6 SD-SPL and 10 DWS patients. PRINCIPAL FINDINGS:Nineteen plasma proteins exhibited significantly different relative concentrations (p<0.05), with five over-expressed and fourteen under-expressed in SD-SPL compared with DWS. The individual protein was classified to either blood coagulation, vascular regulation, cellular transport-related processes or immune response. The immunoblot quantification showed angiotensinogen and antithrombin III significantly increased in SD-SPL whole plasma of early stage compared with DWS subjects. Even using this small number of samples, antithrombin III predicted SD-SPL before shock occurrence with accuracy. CONCLUSION:Proteins identified here may serve as candidate predictive markers to diagnose SD-SPL for timely clinical management. Since the number of subjects are small, so further studies are needed to confirm all these biomarkers.